(untitled) (Al-Mithaq ( Research Journal of Islamic Theology), 2025)
This study examines Prophet Muhammad’s (ﷺ) lessons and practices on love and goodwill, suggesting that these are vital components for fostering harmonious social and family connections. By drawing on Qur’ānic verses, Ḥadīth, and historical instances, it portrays the life of the Prophet (ﷺ) as a paradigm of empathy and insight, highlighting how these principles can transform communities and reinforce family connections. The study is divided into three parts. The initial part lays down the theoretical basis of love and goodwill in Islamic teachings and emphasizes their expression in the Prophet’s (ﷺ) life. The subsequent part addresses the application of these principles in family dynamics, especially in marriage and parenting, referencing the Prophets (ﷺ) dealings with his family. The third part explores the social dimensions of empathy and compassion, emphasizing the Prophet (ﷺ) advice on nurturing harmonious relationships and his inclusive attitude toward kindness, which encompasses both non-Muslims and the environment. The research article concludes by providing practical suggestions for integrating these values into contemporary settings, highlighting their importance in addressing challenges like social fragmentation and family disintegration. This study highlights the exemplary actions of the Prophet (ﷺ), offering a lasting model for promoting love, empathy, and kindness in every aspect of life, inspiring individuals to develop more compassionate and resilient connections.